PROJETO PEDAGÓGICO PARA O DESENVOLVIMENTO DE HABILIDADES DE LEITURA DE QUESTÕES DISCURSIVAS DE PROVAS - Fonseca, Sônia Maria Duque da (Intercâmbio, 2010)
This paper focuses on an educational intervention in which the aim is to develop reading skills on test discursive questions, essential to form citizens capable of interpreting, critical analyses, argumentation, logical reasoning and working solutions out. It also presents some results of a didactic sequence developed as an action-research in a group of Language and Literature students.